Artificial extracellular matrices containing bioactive glass nanoparticles promote osteogenic differentiation in human mesenchymal stem cells - Kroschwald, Lysann M.; Allerdt, Felix; Bernhardt, Anne; Rother, Sandra; Zheng, Kai; Maqsood, Iram; Halfter, Norbert; Heinemann, Christiane; Möller, Stephanie; Schnabelrauch, Matthias; Hacker, Michael C.; Rammelt, Stefan; et al. (International Journal of Molecular Sciences, 2021)
The present study analyzes the capacity of collagen (coll)/sulfated glycosaminoglycan (sGAG)‐based surface coatings containing bioactive glass nanoparticles (BGN) in promoting the osteogenic differentiation of human mesenchymal stroma cells (hMSC). Physicochemical characteristics of these coatings and their effects on proliferation and osteogenic differentiation of hMSC were investigated. BGN were stably incorporated into the artificial extracellular matrices (aECM). Oscillatory rheology showed predominantly elastic, gel‐like properties of the coatings. The complex viscosity increased depending on the GAG component and was further elevated by adding BGN. BGN‐containing aECM showed a release of silicon ions as well as an uptake of calcium ions. hMSC were able to proliferate on coll and coll/sGAG coatings, while cellular growth was delayed on aECM containing BGN. However, a stimulating effect of BGN on ALP activity and calcium deposition was shown. Furthermore, a synergistic effect of sGAG and BGN was found for some donors. Our findings demonstrated the promising potential of aECM and BGN combinations in promoting bone regeneration. Still, future work is required to further optimize the BGN/aECM combination for increasing its combined osteogenic effect.
CRIS-Team Scopus Importer:2021-12-17
Keywords: Artificial extracellular matrices; Bioactive glass nanoparticles; Glycosaminoglycans; Mesenchymal stem cells; Osteogenic differentiation